Street Lighting System for Smart Cities Using Micro-Controllers - Aaquib Parkar; Prashant Kumar Soori (Institute of Advanced Engineering and Science, 2018)
The main goal is to simulate different configurations of street lighting system using DIALux and optimize the energy consumption. Data of the existing road in the United Arab Emirates is considered for simulation. Simulation results are validated by building a hardware model. This is accomplished by using LED modules instead of traditional HPS bulbs which is connected to an Arduino to control different sensors. Photo resistors are used to automatically switch the lights ON or OFF depending on the light intensity. Ultrasonic sensors are used to detect motion of cars and pedestrians in order to switch 50% of the lights off if no motion is detected. The recorded data is monitored by a Raspberry Pi which acting as a monitoring device. Practical measurements were conducted at different points on the road selected and are compared with the simulation results.The main goal is to simulate different configurations of street lighting system using DIALux and optimize the energy consumption. Data of the existing road in the United Arab Emirates is considered for simulation. Simulation results are validated by building a hardware model. This is accomplished by using LED modules instead of traditional HPS bulbs which is connected to an Arduino to control different sensors. Photo resistors are used to automatically switch the lights ON or OFF depending on the light intensity. Ultrasonic sensors are used to detect motion of cars and pedestrians in order to switch 50% of the lights off if no motion is detected. The recorded data is monitored by a Raspberry Pi which acting as a monitoring device. Practical measurements were conducted at different points on the road selected and are compared with the simulation results.